Macrofauna Inhabiting Massive Demosponges From Shallow and Mesophotic Habitats Along the Israeli Mediterranean Coast - Goren, Liron; Idan, Tal; Shefer, Sigal; Ilan, Micha (Frontiers in Marine Science, 2021)
Sponges have long been considered as “living hotels” due to the great diversity and abundance of other taxonomic groups often found in association with them. Sponges are the dominant components of benthic communities in the Levant Sea; and especially in the recently discovered mesophotic sponge grounds off the coast of Israel. However, almost no data exist regarding their associated macrofauna. The current study sought to identify the macrofauna associated with massive sponges along the Israeli Mediterranean coast; and to compare the role of sponges, as ecosystem engineers, or “living hotels”, in both the shallow-water and mesophotic habitats. Sixty-four massive sponge specimens, from 10 different species, were collected from shallow and mesophotic habitats by SCUBA diving and Remotely Operated Vehicle, respectively. Sponge volume was estimated, specimens were dissected, and the associated macrofauna were identified. Our results reveal that the sponges supported a diverse assemblage of associated macro¬fauna. A total of 61 associated taxa were found, including species reported for the first time in Israel. A clear, differentiation existed in the structure of the associated assemblage between the two habitats, which is mainly attributed to four species (two polychaetes, a crustacean, and a brittle star). The trophic composition remained stable across the two habitats. No correlation was found between sponge volume and the associated fauna community parameters. The highest richness of associated fauna was found in the mesophotic habitat, where sponge diversity is also higher. In contrast, a greater endobiont abundance and density were recorded in the shallow habitat, where massive sponges may be a limiting factor due to their lower richness and abundance. Our findings emphasize the importance of sponges as ecosystem engineers, and suggest that sponge diversity may be an important factor that contribute to benthic biodiversity in these regions.